PERAN ORGANISASI AL- JAMI’YATUL WASHLIYAH (AL-WASHLIYAH) DI KOTA MEDAN DALAM PENYEBARAN ISLAM DI INDONESIA - Ika Purnamasari; Arzetti Silaban; Injilia Crist Yolanda; Melli Diara Br Gajah; Nayla Raysha Sarif Simanjuntak; Zulfadhli Lubis (STKIP Subang, 2026)
This study examines the role of Al-Jam’iyatul Washliyah in the spread of Islam in Indonesia, focusing on how Al-Washliyah, as an Islamic organization, contributed to the process of Islamization. The research objectives include uncovering the organization's history, its da'wah development strategies such as establishing madrasahs and adapting to local cultures in areas like Toba Batak and efforts to preserve museum buildings designated as cultural heritage in 2024. The methodology employs a descriptive qualitative approach with deductive analysis, data collection through literature studies, observation, and structured as well as open interviews with museum curator Silmi on March 11, 2026, at the Al-Washliyah Museum in Medan. The findings reveal that Al-Washliyah emerged from the initiatives of figures like Sheikh Muhammad Ya’kub and the waqf of Datuk Muhammad Ali; it managed hundreds of schools by 1941, spread da'wah to Mentawai, Karo, and abroad and implemented cultural adaptation strategies, aqidah development, and supervision to prevent apostasy. The museum faces challenges such as a lack of original artifacts but serves as an open educational center for the wider community.